2015
DOI: 10.1016/j.febslet.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Communication between circadian clusters: The key to a plastic network

Abstract: a b s t r a c tDrosophila melanogaster is a model organism that has been instrumental in understanding the circadian clock at different levels. A range of studies on the anatomical and neurochemical properties of clock neurons in the fly led to a model of interacting neural circuits that control circadian behavior. Here we focus on recent research on the dynamics of the multiple communication pathways between clock neurons, and, particularly, on how the circadian timekeeping system responds to changes in envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 98 publications
0
33
0
1
Order By: Relevance
“…This view was recently challenged, as several groups showed that the morning oscillator is not capable of coherently resetting free-running rhythms when its clock speed is genetically altered and revealed that clock neurons other than the morning oscillator (e.g., the evening oscillator) have independent control over free-running rhythms (Beckwith and Ceriani, 2015; Guo et al, 2014; Yao and Shafer, 2014). It remains unaddressed whether there is a minimal set of clock neurons that can function as a master pacemaker for the entire clock network, driving behavioral rhythms with their endogenous rhythm, despite discrepant timekeeping in the remaining neuronal oscillators.…”
Section: Resultsmentioning
confidence: 99%
“…This view was recently challenged, as several groups showed that the morning oscillator is not capable of coherently resetting free-running rhythms when its clock speed is genetically altered and revealed that clock neurons other than the morning oscillator (e.g., the evening oscillator) have independent control over free-running rhythms (Beckwith and Ceriani, 2015; Guo et al, 2014; Yao and Shafer, 2014). It remains unaddressed whether there is a minimal set of clock neurons that can function as a master pacemaker for the entire clock network, driving behavioral rhythms with their endogenous rhythm, despite discrepant timekeeping in the remaining neuronal oscillators.…”
Section: Resultsmentioning
confidence: 99%
“…The six groups of PER‐TIM‐expressing neurons include the large and small ventral lateral neurons (l‐LNvs and s‐LNvs), the dorsal lateral neurons (LNds), the lateral posterior neurons (LPNs) and three groups of dorsal neurons (DN1s, DN2s and DN3s) (Figure ) (Helfrich‐Förster et al., ; Kaneko & Hall, ). Clock neurons between and within groups use a heterogenous set of neuropeptides and neurotransmitters for signaling (reviewed in Beckwith & Ceriani, ).…”
Section: The Circadian Clock Network In Drosophila Brainmentioning
confidence: 99%
“…Neural plasticity, broadly described as the changes in neuronal morphology 1 , cell-cell interaction 2 , and gene expression 3 , allows neurons to efficiently respond and adapt to those environmental challenges. The uniqueness of neurons is highlighted by their exceptionally complex compartmental diversity.…”
Section: Introductionmentioning
confidence: 99%